Effects of nitrogen sources on bacteriocin production by Enterococcus faecium A 2000 - Pantev, A; Kabadjova, P; Valcheva, R; Danova, S; Dousset, X; Haertlé, T; Chobert, J M; Ivanova, I (Folia microbiologica, 2002)
The production of a novel broad-spectrum antimicrobial peptide enterococcin A 2000, active against Gram-positive and Gram-negative microorganisms including Listeria subsp. and Escherichia coli, by Enterococcus faecium strain A 2000 isolated from the surface of traditional Bulgarian yellow cheese "kash-kaval" is considerably influenced by complex nitrogen sources in the production medium. Medium components, especially peptone and yeast extract, and their concentration contributed to the increase in bacteriocin production during the stationary phase (16-46 h) of cultivation even in the absence of one of the components present in the basal cultivation MRS medium.
Keywords: dusík; Peptones; Enterococcus faecium; Bacteriocins; bakteriociny; sýr; Cheese; Yeasts; Escherichia coli; kvasinky; Listeria; Nitrogen; peptony